Genetics of Azoospermia: Current Knowledge, Clinical Implications, and Future Directions. Part I - Sadeghi-Nejad, Hossein; Farrokhi, Farhat (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: We reviewed the most recent advances in the genetics of male infertility focusing on karyotypic abnormalities, obstructive azoospermia, and idiopathic hypogonadotropic hypogonadism. Materials and Methods: To update our previous review, we searched the literature using PubMed and skimmed articles published from January 1998 to November 2006. There were 52, 30, and 41 relevant articles to our subject on karyotypic abnormalities, obstructive azoospermia, and idiopathic hypogonadotropic hypogonadism, respectively. The full texts of these articles and their bibliographic information were reviewed and a total of 93 were used to contribute to this review. Results: The frequency of sperm aneulpoidy in karyotypic abnormalities such as 47,XXY and 47,XYY is higher than that in the healthy individuals, but transmission of the abnormalities to the offspring is rare and the outcomes of assisted reproductive techniques are encouraging. Mutations in the cystic fibrosis gene are detectable in up to 80% of men with congenital bilateral absence of the vas deferens. However, there is a considerable diversity among different populations and the role of other potential causes is not ruled out yet. Autosomal and X-linked genetic aberrations in men with idiopathic hypogonadotropic hypogonadism are now well known. As hormone replacement therapy can provide the chance of fathering children in these patients, the risk of mutations’ transmission, especially the autosomal dominant ones, is high. Conclusion: In the recent decade, a parallel progress has been made in the understanding of the genetics of men with azoospermia and the treatment modalities for these patients. Assisted reproductive techniques can help most of the patients, but there are several genetic abnormalities that must be considered before decision making for treatment of their infertility.